Description of Apheledessa gen. nov. (Hemiptera: Heteroptera: Pentatomidae: Edessinae) with two new species from the Brazilian Atlantic Forest - Souza, Luiza Fagundes Rodrigues De; Ferreira, Adiney Ferreira; Fernandes, José Antônio Marin (Zootaxa, 2026)
The new genus Apheledessa gen. nov., described here, comprises two new species: Apheledessa absens sp. nov. and Apheledessa inopia sp. nov. The genus is diagnosed based on a unique combination of characters, including well-developed, subrectangular, dorsoventrally flattened humeral angles, and a metasternal process with the anterior portion medially perforated and posteriorly sloping. Both species occur in the Atlantic Forest biome, with records from mountainous areas of the states of Rio de Janeiro and Santa Catarina, Brazil. Diagnoses, descriptions, and a distribution map are provided. Illustrations of the habitus in dorsal and ventral views, as well as of the male pygophore and female genital plates, are also provided.